Aldehyde dehydrogenase 1A3 influences breast cancer progression via differential retinoic acid signaling. Issue 1 (24th July 2014) - Marcato, Paola; Dean, Cheryl A.; Liu, Rong-Zong; Coyle, Krysta M.; Bydoun, Moamen; Wallace, Melissa; Clements, Derek; Turner, Colin; Mathenge, Edward G.; Gujar, Shashi A.; Giacomantonio, Carman A.; Mackey, John R.; et al.
Abstract : Aldehyde dehydrogenase (ALDH) 1A enzymes produce retinoic acid (RA), a transcription induction molecule. To investigate if ALDH1A1 or ALDH1A3‐mediated RA signaling has an active role in breast cancer tumorigenesis, we performed gene expression and tumor xenograft studies. Analysis of breast patient tumors revealed that high levels of ALDH1A3 correlated with expression of RA‐inducible genes with retinoic acid response elements (RAREs), poorer patient survival and triple‐negative breast cancers. This suggests a potential link between ALDH1A3 expression and RA signaling especially in aggressive and/or triple‐negative breast cancers. In MDA‐MB‐231, MDA‐MB‐468 and MDA‐MB‐435 cells, ALDH1A3 and RA increased expression of RA‐inducible genes. Interestingly, ALDH1A3 had opposing effects in tumor xenografts, increasing tumor growth and metastasis of MDA‐MB‐231 and MDA‐MB‐435 cells, but decreasing tumor growth of MDA‐MB‐468 cells. Exogenous RA replaced ALDH1A3 in inducing the same opposing tumor growth and metastasis effects, suggesting that ALDH1A3 mediates these effects by promoting RA signaling. Genome expression analysis revealed that ALDH1A3 induced largely divergent gene expression in MDA‐MB‐231 and MDA‐MB‐468 cells which likely resulted in the opposing tumor growth effects. Treatment with DNA methylation inhibitor 5‐aza‐2'deoxycytidine restored uniform RA‐inducibility of RARE‐containing HOXA1 and MUC4 in MDA‐MB‐231 and MDA‐MB‐468 cells, suggesting that differences in epigenetic modifications contribute to differential ALDH1A3/RA‐induced gene expression in breast cancer. In summary, ALDH1A3 induces differential RA signaling in breast cancer cells which affects the rate of breast cancer progression. Highlights: RA‐inducible gene expression in breast cancer is dependent on ALDH1A3 expression. Triple‐negative breast cancer patients have higher expression of ALDH1A3. ALDH1A3 determines breast tumor progression by inducing RA signaling. Opposing tumor growth effects of ALDH1A3/RA is due to differential gene expression. DNA methylation contributes to differential gene expression induced by ALDH1A3/RA.